Políticas públicas da intervenção precoce para o Transtorno do Espectro Autista (TEA) na educação infantil - Pinto, Laura Silva (Brasil, 2023)
This study discusses the results of research still in progress, with the perspective of understanding the concepts about ASD and early intervention and knowing the history and the legal frameworks of early stimulation in the school context. The interest emerges from the context of increased discussion about ASD or children with spectrum characteristics, and from the consequent need to broaden debate about the importance of early intervention in daycare centers and preschools, taking into account the neuroplasticity of early childhood. The methodological approach adopted for the analysis is qualitative in nature, using bibliographic and documentary research. The results of the study show that with the struggles, public policies were established aiming to ensure stimulation in public schools, especially in day care centers and preschools, with a view to intervening when noticing the warning signs in development delas.